Innate immune response during NTM infections - Sousa, Sara (2015)
Background As tuberculosis incidence declines in industrialized countries, nontuberculous mycobacteria (NTM) infections gained relevance. Human infection with NTM became relevant with AIDS pandemic, being currently recognized as a cause of pulmonary infection in humans. Despite this fact little is known about NTM pathogenesis. In the present work the role of innate immune response during NTM infection using THP-1 cells as a model of alveolar macrophages was evaluated. Methods M.smegmatis mc2 155, 2 reference strains (M.avium ATCC25291; M.fortuitum ATCC6841) and 2 clinical isolates (M.avium 60/08;M. fortuitum 747/08) were used. Bacteria were grown until mid-exponential phase and stored at -80°C. Before each experiment analiquot was thawed and diluted in RPMI with 10% HI- FCS in order to reach an OD600nm of 0.1. The inoculums were titrated by CFU enumeration on 7H10 medium supplemented with 10% OADC. Briefly, 4x104 THP-1 cells were platted/well and incubated for 72h with 100nM PMA (37°C/5% CO2) then fresh medium without PMA was added being the cells incubated for further 24h. The cells were infected for 1 or 3h for fast or slow growers, respectively. The intracellular persistence was evaluated by CFU enumeration at different time points from 1 to 24h or 3 to 168h for fast and slow growers, respectively. Phagosome acidification was followed using confocal microscopy. The secretion of pro-inflammatory cytokines was assayed by ELISA, NO production using the Griess reagent and apoptosis was followed by flow cytometry and confocal microscopy. The ability of mycobacteria to persist at different pHs was evaluated using BACTEC-MGIT960. Results The mycobacteria experienced different fates within THP-1 macrophages. M.smegmatis and M.fortuitum ATCC6841 were cleared within 24h, whereas 747/08 and the two M.avium strains were able to replicate. Despite this fact for the latest mycobacteria more than 50% of acidified phagosomes were present during the experience. Mycobacteria survival at acidic pHs (6.6; 5.4 and 4.6) was then evaluated. With the exception of M.smegmatis all strains grew at acidic pH showing that other factors than phagosome acidification were involved in mycobacteria killing. Next, other components of the inflammatory response were evaluated. Measurable values of NO were present in supernatants of THP-1 infected for 3 days with 60/08 being this bacterium susceptible, to high concentrations of NO in vitro. Il-10 secretion was also assayed. For both fast growing NTM and M.avium ATCC25291 the production of IL-10 was not detectable. For 60/08 IL-10 production peaked at 3 days, decreasing afterwards until undetectable levels at 7 days. Another factor being explored is apoptosis induction by NTM. Our preliminary results point to differential induction of apoptosis by different NTM.